Development of Ethosomes for the Topical Treatment of Androgenic Alopecia: Ethanol Effect on Dutasteride Targeting to the Hair Follicles - Jayanaraian F. M. Andrade; Rafael V. Rocho; Breno N. Matos; Geisa N. Barbalho; Kariane M. Nunes; Marcilio Cunha-Filho; Guilherme M. Gelfuso; Tais Gratieri (Pharmaceutics, 2025)
Background/Objectives: Treatment options for androgenic alopecia are still very limited and lack long-term efficacy. Dutasteride (DUT) has gained interest as a potent inhibitor of 5α-reductase, allowing for spaced applications, but DUT oral intake can cause serious adverse effects. Herein, we developed, characterized, and assessed the potential of DUT-loaded ethosomes with increasing ethanolic concentrations for hair follicle (HF) targeting to treat androgenic alopecia, hypothesizing that ethanol’s interaction with HFs’ sebum might increase DUT targeting to the HFs. Methods: Ethosomes were obtained using the water-dropping method. After a hydrodynamic size screening, a 30% ethanol concentration was fixed. Ethosomes with 30% ethanol were also prepared and had their ethanolic content removed by rotary evaporation for the evaluation of ethanol in targeting DUT to the HFs. The targeting factor (Tf) was calculated as the ratio between the DUT amount in HFs and the total DUT amount recovered from all skin layers after in vitro porcine skin penetration tests for 12 and 24 h. Results: The ethanolic concentration affected the vesicles’ size and the targeting potential. While the dried ethosomes could not increase DUT accumulation in the HFs at both time points (Tf: 0.27 in 12 h and Tf: 0.28 in 24 h), the presence of 30% ethanol in the vesicles increased the Tf from 0.28 (12 h) to 0.34 (24 h), significantly superior (p < 0.05) than the dried ethosome and control (Tf: 0.24) in 24 h. Conclusion: Ethosomes with a 30% ethanolic concentration were slightly more efficient in targeting HFs for dutasteride delivery.